À propos du malkʾa Maryam et de l’occident (Suivi de deux notes d’hagiographie) - Beylot, Robert (Aethiopica, 2005)
Latin medieval parallels to the malkʾa Maryam were reported in a previous paper. Since, a french scholar issued a study about Mary’s place in the medieval liturgy and her physical presence in the liturgical symbolic. So the latin texts in question are replaced in a whole. The possibility of a continuation until the Renaissance is explored. In the baroque ages we find in France a marial association from bavarian origin, internationally represented whose devotions are alike that inspiring the malkʾa Maryam. A further research is necessary about this parallel development of piety in Europe and Ethiopia. The miracle of the light expanded by the saint’s fingers during the prayer is listed from a few ethiopic lives. A few comments are given about Marrassini’s edition from the Gädlä Gäbrä Mänfäs Qeddus, especially the names of the saint’s fathers. Two toponyms of the same Gädl are examined and an alternative reading of the considered sentence is suggested.